2015
DOI: 10.1021/sc5008303
|View full text |Cite
|
Sign up to set email alerts
|

A Recyclable Acidic Ionic Liquid Gel Catalyst for Dehydration: Comparison with an Analogous SILP Catalyst

Abstract: An acid-functionalized ionic liquid was entrapped within a silica gel to yield a recyclable liquid phase catalyst for the dehydration of rac-1-phenyl ethanol. Hot filtration tests showed that the activity was within the gel. Comparison with an analogous SILP system revealed fundamental differences in the properties and behavior of the materials.The discovery of facile ionic-liquid silica gel formation, 1,2 enabled the introduction of the first ionic liquid mediated sol-gel methods for the preparation of solid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 52 publications
0
42
0
Order By: Relevance
“…3,4,5 More recently the autocatalytic synthesis of ionic liquid gels was introduced using an acidic ionic liquid. 6 Occasionally ionic liquid gels have been synthesised using neutral ionic liquids, with an additional base as the catalyst, 7 but these materials are reported to have low mechanical strength. Potential advantages of developing basic routes to ionic liquid gels are demonstrated by the application of basic ionic liquid SILPs (Supported Ionic Liquid Phases).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3,4,5 More recently the autocatalytic synthesis of ionic liquid gels was introduced using an acidic ionic liquid. 6 Occasionally ionic liquid gels have been synthesised using neutral ionic liquids, with an additional base as the catalyst, 7 but these materials are reported to have low mechanical strength. Potential advantages of developing basic routes to ionic liquid gels are demonstrated by the application of basic ionic liquid SILPs (Supported Ionic Liquid Phases).…”
mentioning
confidence: 99%
“…10 Building on the understanding gained from our work on autocatalytic systems for acidic ionic liquid gels, 6 our hypothesis was that the combination of a viscous ionic liquid with the right level of Brønsted basicity could slow down the sol-gel process, and allow a more controlled sol-gel reaction. We found that, by careful selection of Brønsted basic ionic liquid, we were able to tame the sol-gel reaction to form silica and titania ionic liquid gels on a slower time frame.…”
mentioning
confidence: 99%
“…27 Of the gels presented here several have been successfully formulated from functional ionic liquids which have shown promise in diverse applications. 28 : acidic catalytic membranes. In some of these applications the ionic liquid could be made more easily applied in the gel state.…”
Section: Introductionmentioning
confidence: 99%
“…%. An interesting observation is seen with [TEAPS][NTf 2 ], an acidic ionic liquid,28 where 1 did not gel at 4 wt. % but 2 did.…”
mentioning
confidence: 98%
“…Recently, Marr and co‐workers have developed a recyclable acidic ionic liquid gel catalyst for the dehydration of rac ‐1‐phenyl ethanol. It was reported that this ionic liquid gel demonstrated significantly improved activity as well as negligible leaching . In this work, we described the application of an analogue of this Brønsted acidic ionic liquid gel for the preparation bis(indolyl)methanes from aldehydes and indoles via Friedel–Crafts alkylation assisted by sonication under solvent‐free condition.…”
Section: Introductionmentioning
confidence: 99%